Endoscopic transpterygoid nasopharyngectomy: Correlation of surgical anatomy with multiplanar CT1. Issue 5 (19th June 2012) - Hosseini, Seid Mousa Sadr; McLaughlin, Nancy; Carrau, Ricardo L.; Otto, Bradley; Prevedello, Daniel M.; Solares, C. Arturo; Zanation, Adam M.; Kassam, Amin B.
Abstract Background Oncologic resection of the nasopharynx is challenging due to its complex and deep‐seated nature. We aimed to illustrate the anatomic landmarks of endoscopic nasopharyngectomy and design a surgical training model that could facilitate learning of this technique. Methods An endoscopic endonasal dissection of the nasopharynx was completed in fresh cadaveric specimens under conditions similar to those of our operating suite. Digital data from a high‐resolution CT scan were imported to an image guidance system to be used during the dissections. Results We expanded the sinonasal corridor, harvested a contralateral nasoseptal flap, and exposed the pterygopalatine and infratemporal fossae. A detailed anatomic dissection of the nasopharynx was correlated to multiplanar images provided by the image guidance system, highlighting appropriate bony, neural, and vascular landmarks. Conclusions Understanding the anatomy‐based endoscopic modular approaches facilitates planning and safe execution of an oncologic nasopharyngectomy. Clinical experience remains mandatory because anatomic models fall short of clinical scenarios. © 2012 Wiley Periodicals, Inc. © 2012 Wiley Periodicals, Inc. Head Neck, 2013